Tanggung Jawab Penjual Terhadap Pembeli Terkait Jual Beli Online Dengan Sistem Pre Order - Hisbollah, Alif Adnan; Tjoanda, Merry; Balik, Agustina (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Online buying and selling transactions are permitted by law, as there is a principle of freedom to contract stated in Article 1338 of the Civil Code, as long as it does not violate the provisions of Article 1337 of the Civil Code. However, there are still people who violate the agreements made, causing losses due to non-performance by the seller/business actor, namely NAMAStudios brand, to the buyer, by not delivering the ordered goods.Purposes of the Research: Explaining the seller's responsibility in breach of contract in online buying and selling with a pre-order system, and the dispute resolution by the affected buyer in online buying and selling with a pre-order system.Methods of the Research: The research methodology used is juridical normative. A juridical normative research is a type of research that examines legal materials, legal doctrines, legal principles, legal norms, and positive legal provisions to address the legal issues being studied.Results of the Research: Article 19 of the Consumer Protection Law states that business actors are responsible for damages and losses suffered by consumers caused by the goods or services they trade. The seller can be held liable both contractually and by risk. In dispute resolution, there are two avenues that can be taken: litigation and alternative dispute resolution, in accordance with Article 38 of the ITE Law and Article 39 of the Consumer Protection Law. Consumer dispute resolution can be done through the court or alternative dispute resolution in accordance with Article 45 of the Consumer Protection Law. In terms of litigation, consumers can file a lawsuit through a class action in accordance with Article 46 paragraph (1) point 2, while non-litigation alternative avenues can be through the Consumer Dispute Settlement Agency (BPSK), also regulated in the Consumer Protection Law.